PENGARUH KECEPATAN TERHADAP BIAYA ANGKUTAN KAPAL TANKER - Denny Najoan; Aprilya Bomadayanti Ariesta; Yosi Pahala (Institut Transportasi dan Logistik Trisakti, 2018)
The aim of this research is to prove the effect of speed to the cost of transportation. The research problems are how much the effect of the ship speed, how much the cost for distributing fuel, how much the fuel consumption, what threat factors that will influence the cost, and operational design in ship distribution. The analysis of the data used linear regression statistical analysis, correlation coefficient analysis, the determinant coefficient analysis and hypothesis test. The samples of the data were 32 voyage ships. The result shows that the ship speed is fast, in fact it is faster than guaranteed speed so that it gives impact to the fuel cost due to the increase of fuel consumption.